Theft Victimization in Urban Settings: Comparison of Tourist and Resident Case Profiles - Marteache, Nerea (Crime & delinquency, 2024)
The relationship between urban tourism and crime has been well documented, although a focus on the specifics of tourist victimization is lacking. This study explores police-recorded thefts against urban tourists in the city of Barcelona (Spain). We apply Conjunctive Analysis of Case Configurations to a large data sample to uncover victimization case profiles and the context in which crimes are committed. Comparisons to resident victimization reveal that the case profiles most likely to result in a tourist being the victim of theft have predominantly female, young targets, and occur mostly at restaurants/bars and during the Summer. Future research should examine victimization trends while accounting for time spent in different settings, and compare self-protective behaviors taken by tourists and residents.